Development and Rasch Validation of the Indonesia College Pornography Consumption Scale (CPCS) - Rahmatullah, Bagas; Rahmani, Aliya; Afriliana, Wenny; Kusuma, Raitani Ambar; Mantika, Siti Hawa Annisa; Rosyadi, Muhammad Farhan (Universitas Negeri Surabaya, 2026)
Background: Online pornography raises concerns about problematic use among university students. Existing measures lack validation for Indonesian populations. Objective: To develop and validate the College Pornography Consumption Scale (CPCS) for Indonesian students. Method: Guided by Griffiths’(2005) biopsychosocial addiction model, an item pool covering six dimensions was generated and reviewed by expert judges. Psychometric evaluation used Rasch analysis on data from 383 Indonesian undergraduates recruited via purposive sampling. Results: Rasch analysis supported unidimensionality (variance explained = 66.20%). Reliability indices were high (person separation reliability = .95; Cronbach’s α = .98). Most items demonstrated acceptable model fit; however, eight misfitting items require refinement. The Wright map indicated effective targeting across levels of addictive behaviors, with greater sensitivity at higher levels of problematic use. Conclusion: Initial findings provide support for the validity of the CPCS, though the eight misfitting items indicates that the scale's performance is still being optimized. CPCS offers a useful starting point for clinical screening in Indonesia population, provided that future iterations re-evaluate the problematic items to improve overall model fit. Abstrak Latar Belakang: Akses ke pornografi daring semakin mudah, menimbulkan kekhawatiran tentang penggunaan problematik di kalangan mahasiswa. Instrumen yang ada belum tervalidasi khusus untuk populasi Indonesia. Tujuan: Mengembangkan dan memvalidasi College Pornography Consumption Scale (CPCS) bagi mahasiswa Indonesia. Metode: Berpedoman pada model adiksi biopsikososial Griffiths (2005), disusun himpunan butir yang mencakup enam dimensi (saliensi, toleransi, modifikasi suasana hati, gejala putus, konflik, kekambuhan) dan ditinjau oleh pakar. Evaluasi psikometrik menggunakan analisis Rasch pada data 383 mahasiswa sarjana Indonesia yang direkrut melalui sampling purposif. Hasil: Analisis Rasch mendukung unidimensionalitas (66,20%). Indeks reliabilitas tergolong tinggi (person separation reliability = .95; α = .98). Sebagian besar item menunjukkan kesesuaian model yang dapat diterima; namun, delapan item yang misfit memerlukan penyempurnaan. Wright Map menunjukkan penargetan yang efektif di berbagai tingkat perilaku adiktif, dengan sensitivitas yang lebih besar pada tingkat penggunaan bermasalah yang lebih tinggi. Kesimpulan: Temuan awal mendukung validitas CPCS, meskipun beberapa item masih perlu disempurnakan. Skala ini berpotensi menjadi instrumen awal untuk menilai penggunaan pornografi bermasalah pada mahasiswa Indonesia, dengan kebutuhan pengembangan lanjutan guna meningkatkan kesesuaian model.